An Overview of the Special Party Menu Handling at the Nangroe Saka Hotel Medan Restaurant - Naiborhu, Marintan (Cattleya Darmaya Fortuna, 2024)
A special party menu is commonly referred to as Table d'hôte, which is a complete set menu consisting of an appetizer, soup, main course, and dessert. The successful presentation of a special party menu requires proper service, knowledgeable waitstaff, and the active role of a supervisor throughout its execution. This study was conducted through observations and interviews with 23 individuals at Saka Hotel Medan, including 6 kitchen staff, 5 waitresses, 10 guests, and 2 members of hotel management. Based on the data collected, the authors conclude that the shortcomings in handling the special party menu stem from delays in food service, limited knowledge among waitstaff regarding proper service procedures, and insufficient involvement of the supervisor during the event’s execution.